2018
DOI: 10.4321/s0376-78922018000200006
|View full text |Cite
|
Sign up to set email alerts
|

Estudio económico del tratamiento de las quemaduras térmicas mediante desbridamiento enzimático; papel determinante de la estancia hospitalaria

Abstract: Introducción y Objetivo. La caída del cabello y la pérdida de respuesta de nuestro organismo, obedece a una serie de desórdenes bioquímicos que en poco tiempo afectan irreversiblemente a la estructura microscópica del folículo piloso. Hasta ahora estos factores desencadenantes no han sido identificados de manera clara, y en teoría los factores de crecimiento podrían ayudar a estabilizar el complejo del folículo piloso al brindarle mayor oxigenación y nutrición por medio de la neovascularización.El objetivo del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Similarly, a cost analysis was performed by Giuduce et al who estimated savings worth 53 300€ by using NXB in ten patients 99 . Martinez‐Mendez et al found that hospital length of stay was the main cost determinant and the actual cost of NXB was only 13.9% of the total treatment cost 100 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a cost analysis was performed by Giuduce et al who estimated savings worth 53 300€ by using NXB in ten patients 99 . Martinez‐Mendez et al found that hospital length of stay was the main cost determinant and the actual cost of NXB was only 13.9% of the total treatment cost 100 …”
Section: Discussionmentioning
confidence: 99%
“…Since then, approximately 10 000 patients have been successfully treated with NXB for deep thermal burns. European consensus guidelines 39,40 and individual European country guidelines have been published, including Spain, 41,42 Italy, 43 Romania, 44 and Poland 45 . It is currently approved for use in forty‐four countries worldwide, most recently in the United States, 46 and in pre‐approval stages in Australia 47…”
Section: Introductionmentioning
confidence: 99%
“…Following the 2017 Spanish consensus guideline on enzymatic debridement in burn injuries, 14 the medical team assessed whether the burn required conservative treatment, with a potential for spontaneous epithelialization or surgery (Table 1 and Fig. 1).…”
Section: Methodsmentioning
confidence: 99%